Enhancing the study on pediatric sleep hygiene - Borkar, Priyanka K.; Gawarle, Neha (International Journal Of Community Medicine And Public Health, 2024)
The article delves into various aspects such as school performance, BMI, and sleep habits. However, it doesn’t provide additional demographic details like gender or grade level, apart from mentioning the participants’ ages. A study done by Mandy Pascalle Glasbeek et al shows that sleep reduction is more common in girls and older aged adolescents. Sleep is essential for promoting development, brain function, and emotional control from infancy onward. The study’s conclusions are concerning as well as illuminating. In the study more than half of the children who took part had poor sleep quality, it is clear that pediatric healthcare providers should pay more attention to sleep hygiene. The link between poor sleep quality and both childhood weight and poor academic achievement is especially concerning. The results highlight the complex relationship between sleep and children’s general health and wellbeing.